Direct access to millions of mutations by whole genome sequencing of an oilseed rape mutant population. (19th January 2023) - Jhingan, Srijan; Kumar, Avneesh; Harloff, Hans‐Joachim; Dreyer, Felix; Abbadi, Amine; Beckmann, Katrin; Obermeier, Christian; Jung, Christian
SUMMARY: Induced mutations are an essential source of genetic variation in plant breeding. Ethyl methanesulfonate (EMS) mutagenesis has been frequently applied, and mutants have been detected by phenotypic or genotypic screening of large populations. In the present study, a rapeseed M2 population was derived from M1 parent cultivar 'Express' treated with EMS. Whole genomes were sequenced from fourfold (4×) pools of 1988 M2 plants representing 497 M2 families. Detected mutations were not evenly distributed and displayed distinct patterns across the 19 chromosomes with lower mutation rates towards the ends. Mutation frequencies ranged from 32/Mb to 48/Mb. On average, 284 442 single nucleotide polymorphisms (SNPs) per M2 DNA pool were found resulting from EMS mutagenesis. 55% of the SNPs were C → T and G → A transitions, characteristic for EMS induced ('canonical') mutations, whereas the remaining SNPs were 'non‐canonical' transitions (15%) or transversions (30%). Additionally, we detected 88 725 high confidence insertions and deletions per pool. On average, each M2 plant carried 39 120 canonical mutations, corresponding to a frequency of one mutation per 23.6 kb. Approximately 82% of such mutations were located either 5 kb upstream or downstream (56%) of gene coding regions or within intergenic regions (26%). The remaining 18% were located within regions coding for genes. All mutations detected by whole genome sequencing could be verified by comparison with known mutations. Furthermore, all sequences are accessible via the online tool 'EMSBrassica' (http://www.emsbrassica.plantbreeding.uni‐kiel.de ), which enables direct identification of mutations in any target sequence. The sequence resource described here will further add value for functional gene studies in rapeseed breeding. Significance Statement: We report on the distribution of induced mutations across a complex crop genome. We found that mutations are non‐randomly spread across the genome. Moreover, the manuscript describes a suitable approach and presents an online database for identifying rapeseed ethyl methanesulfonate mutants on a whole genome scale. This will serve as a valuable resource for rapeseed functional genomics and breeding.